Tuesday

October 21, 2014

October 21, 2014

Posted by **Nelly** on Thursday, September 8, 2011 at 6:39am.

g:x--> 2x+3/x-4

h:x --> 1/x

Write expressions for :

a) hg(x)

b) g inverse 1(x)

- MATH HELP -
**Reiny**, Thursday, September 8, 2011 at 8:48amI noticed from the "related Questions" below that you have posted this same question several times.

One of the reasons that you have not received an answer could be that your expression is ambiguous.

Do you mean (2x+3)/(x-4) or do you mean it to be as you actually typed it.

Also your expression of hg(x) is not expressed in a standard form

you often see it as h∘g(x) or h(g(x))

It looks like you just want the two functions multiplied.

If you just wanted the multiplication, then

your hg(x) = (1/x)(2x+3)(x-4)

and then you would expand and simplify that.

Lastly I am not sure what you mean by

g inverse 1(x) , do you want the inverse of g(x)?

that would be written as g^-1 (x)

Before I proceed, please clarify your question.

**Answer this Question**

**Related Questions**

MATH - Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x ...

MATH - Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x ...

MATH - Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x ...

MATH HELP - Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x -->...

math(functions) - Find the inverse of f for which f is defined as f:x-(2x minus ...

Math - Inverse Functions - Find the inverses of the following functions. y = 3(x...

Algebra - The directions to a problem say "write two equivalent expressions for ...

Algebra - The directions to a problem say "write two equivalent expressions for ...

add maths - Two functions f and g are defined by f:x→3x+2 and g:x→x^...

math - The application of one function followed by the application of a second ...